REKAYASA MEDIA TANAM TERHADAP PERTUMBUHAN, KELANGSUNGAN HIDUP DAN PRODUKSI SAYURAN - Nur Rahmah; Mohammad Wijaya; Patang Patang (Universitas Negeri Makassar, 2015)
The purpose of this research is aim to know the influence of cultivating-media of combustion-soil a giving compost toward growth reaction, viability, and vegetables production. This research was used a complete-randomly plan that consist of three treatment included P1 with combustion-soil adding by 65.625 g (15 tons/ha) of compost, P2 with combustion-soil adding by 109.375 g (25 tons/ha) of compost, P3 with combustion-soil adding by 153.125 g (35 tons/ha) of compost, and a combustion-soil as a control. This experiment was done three times until it was gotten 12 units of experiment. The data gotten were analyzed by using multifariously-examination analysis manually. The result of the research showed that the treatment toward P3 with combustion-soil adding by 153.125 g (35 tons/ha) of compost was the best treatment for a high-plant parameter, leaf number, and gross weight. While for viability, P1 was the best treatment with 100 % percentage of viability